Chairman of VLIK Mykolas Krupavičius and His Ideas for Liberation of Lithuania - Banionis, Juozas (Genocidas ir rezistencija, 2022)
Thirty years ago, in 1992, the Supreme Committee for the Liberation of Lithuania (VLIK) announced of termination of its activities as its main purpose – liberated Lithuania – was accomplished.This organisation, which had turned from an anti-Nazi to an anti-Soviet organisation and had taken on the burden of liberating the homeland, had set itself the goal of forming a Lithuanian government in the diaspora in 1944–1955. During this period, the leader of the VLIK was a priest and a distinguished politician Mykolas Krupavičius (1885–1970). Not only did he put every effort in pursuing this main goal for the sake of the homeland but he also raised and developed ideas for liberation of Lithuania.The VLIK, which was restored in West Germany, consisted of political parties that had been active in parliamentary Lithuania and the resistance movements that had already emerged in occupied Lithuania. They formed Christian and secularist blocs; however, disagreements between them threatened the unity of the work of Lithuanian liberation. On the other hand, the political parties and the resistance movements that were involved in the VLIK demonstrated their mutual trust in the organisation, which united them, by transferring their political power to it. Thus, the VLIK expressed not only the political will of part of the nation (the diaspora) but of the whole nation to win independence and freedom for Lithuania. In this context, the chairman of the VLIK called on all these political groups to unite in support of the idea of liberation of Lithuania.At the beginning of this period, the VLIK, after making amendments to the Declaration of 16 February 1944, issued the Würzburg Protocol on 3 July 1945, according to which the system of the restored independent Lithuania was to be based on the Constitution of 1922. Although there was a great deal of anticipation of a clash between hostile Great Powers at the beginning (in the second half of the 1940s), in the long term the guidelines of the liberation work held high hopes, relying on the principles of the Atlantic Charter as well as on the UN Declaration, and looking forward to the Peace Conference. Promoting the cause of Lithuania’s freedom, the VLIK actively drafted and sent memoranda and statements to the leaders of the USA, Great Britain and other major democracies. In addition to the aspirations of the Lithuanian people, the documents expressed concern about the situation in the occupied country, namely, the ongoing armed resistance struggle, the mass deportations of the population, and the fate of the Lithuanians who had fled to the West.As mentioned above, one of the main aims objectives of the VLIK’s activities in the given period was to organise the Lithuanian government in exile, which required the settlement of relations with the Lithuanian diplomatic service (LDS) which embodied the guarantor of the constitutional continuity of the state. Meetings between the two institutions have been held for this purpose. Nevertheless, it has to be admitted that no agreement on any specific manifestations of representation of the interests of Lithuania as a state was reached between the VLIK and the LDS. The attempt to create an exilic authority relying on the Lithuanian Constitution dated 1922 and consisting of the VLIK, which performed the “functions of the Seimas and the President of the Republic”, and the Executive Council (VT), which corresponded to the “Government, the Cabinet of Ministers”, was unsuccessful. After the discovery in Washington in 1954 that the US “[did] not practice official recognition of such organisations”, the idea of setting up a Lithuanian government in exile was abandoned at the end of the 1950s.In the 1940s, however, the VLIK managed to fend off the claims of the new entity, the Supreme Committee for the Reconstruction of Lithuania (VLAK), which declared itself “the supreme political and military leader of the work of reconstruction of the state”. At a meeting of representatives of the VLIK, the VT and the Lithuanian resistance organised in Baden-Baden on 7–9 July 1948, it was agreed that the VLIK and the VT would lead the struggle for the liberation of Lithuania abroad. At the same time, the VLIK assumed the right to represent the resistance, and when international circumstances changed in the early 1950s, the Lithuanian partisans were urged to protect their lives and rely on the diaspora which would continue to pursue the issue of the freedom of the homeland through political and diplomatic means.By gathering Lithuanians – political refugees – into the Lithuanian World Community (Lith. PLB), Krupavičius became the founder of this organisation and performed an important work in our history. The Lithuanian Charter published on 14 June 1949 laid the foundations of the ideology of Lithuanians all over the world, emphasising two main (“primary and incidental”) goals for the compatriots, namely, to preserve Lithuanian identity and to “regain freedom for Lithuania”.In modelling the future of Lithuania, Krupavičius envisaged a “secularist” path for Lithuania, but urged that Christianity should not be abandoned, otherwise materialism would take its place.
Keywords: soviet occupation; emigree; resistance; VLIK; political refugees